"Only when it's written here": personal writing as testimony in the aftermath of childhood sexual abuse. Issue 3 (3rd July 2021) - Sagi, Bella
ABSTRACT: The article presents a narrative qualitative study that included analysis of 54 texts written and published online by 22 women aged 20–40 who had been sexually abused in childhood. The study found that personal writing by victims of childhood sexual abuse fosters rehabilitation of the damaged witness function within the post-traumatic mind by self-testimony processes that occur in various forms in the writing. Writing facilitates different aspects within conflicting experiences, as shows through the theme of silence and speech. I shall also address the unique role of images and metaphors in trauma processing. The theoretical contribution of the study to the field of bibliotherapy and poetry therapy is in understanding the role and meanings of writing in processes of coping with abuse and constructing self-cohesion as well as in the significance of combining writing and metaphorical work in therapy with victims of childhood sex abuse.